INVESTIGATION OF THE DYNAMICS OF MACHINE AGGREGATES WITH HIGH GEAR RATIO GEARBOXES - R.U. Siddiqov (Modern American Journals, 2025)
This scientific article presents the results of a comprehensive study of the dynamic characteristics of machine aggregates equipped with gearboxes with high gear ratios. The main objective of the research is to identify ways to improve the reliability, stability, and efficiency of gearboxes operating under high dynamic loads. As a result of the conducted studies, practical recommendations were developed to reduce vibrations of gearbox components, minimize transmission errors, and enhance overall energy efficiency. The research employed innovative approaches such as the use of modern composite materials, dynamic modeling methods, and the optimization of gear micro-geometry.
Keywords: Gearbox dynamics, planetary gearbox, gear ratio, vibration analysis, dynamic modeling, gear micro-geometry, tuning, critical rotational speed, transmission error, energy efficiency.